2010
DOI: 10.1007/s00382-010-0946-4
|View full text |Cite
|
Sign up to set email alerts
|

Snow precipitation at four ice core sites in East Antarctica: provenance, seasonality and blocking factors

Abstract: Snow precipitation is the primary mass input to the Antarctic ice sheet and is one of the most direct climatic indicators, with important implications for paleoclimatic reconstruction from ice cores. Provenance of precipitation and the dynamic conditions that force these precipitation events at four deep ice core sites (Dome C, Law Dome, Talos Dome, and Taylor Dome) in East Antarctica were analysed with air mass back trajectories calculated using the Lagrangian model and the mean composite data for precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 76 publications
(110 reference statements)
11
128
0
1
Order By: Relevance
“…The different levels of 17 O-excess between Vostok, EDC and TD at EH are consistent with unequal modern RH n of the OSR, as expected from our current understanding of 17 O-excess in polar regions. The lower 17 O-excess for TD, compared to the one at EDC, reflects the influence of OSR from higher latitudes and therefore higher RH n (Appendix B; Sodemann and Stohl, 2009;Scarchilli et al, 2010). We explain the unequal evolution of 17 O-excess for Vostok, EDC and TD respectively, with a different glacial/interglacial change in RH n at their respective OSRs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The different levels of 17 O-excess between Vostok, EDC and TD at EH are consistent with unequal modern RH n of the OSR, as expected from our current understanding of 17 O-excess in polar regions. The lower 17 O-excess for TD, compared to the one at EDC, reflects the influence of OSR from higher latitudes and therefore higher RH n (Appendix B; Sodemann and Stohl, 2009;Scarchilli et al, 2010). We explain the unequal evolution of 17 O-excess for Vostok, EDC and TD respectively, with a different glacial/interglacial change in RH n at their respective OSRs.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, the Lagrangian moisture source diagnostics revealed stronger influences of the Pacific and Atlantic sectors for Vostok, compared to EDC, where moisture is mainly coming from the western Indian Ocean sector ( Fig. 4; Appendix B; Sodemann and Scarchilli et al, 2010;Werner et al, 2001). TD shows a completely different pattern, with moisture sources shifted towards the Pacific sector of the Southern Ocean compared to Vostok and EDC (Fig.…”
Section: R Winkler Et Al: Deglaciation Records Of 17 O-excess In Eamentioning
confidence: 99%
“…Accumulation in northern Victoria Land, where the coast faces north, comes primarily from storms in the Indian Ocean (Scarchilli et al, 2011), with the origin of air masses similar to that of adjacent Wilkes Land. However, the Transantarctic Mountains block flow to southern Victoria Land so that this region is influenced by storms that cross the Ross Sea (Sodeman and Stohl, 2009).…”
Section: Victoria Land (Vl)mentioning
confidence: 99%
“…The TALDICE ice core revealed that the Talos Dome site is very sensitive to the climatic variations occurring at regional-to-global scale over the last climate cycle . Particular attention was paid to changes in marine and atmospheric circulation and marine productivity in the Ross Sea and Adelie Land sectors (Scarchilli et al, 2011). Its relatively large accumulation rate (with respect to other ice core sites located on the Antarctic Plateau) enables an accurate dating of the core, particularly during the Holocene (the last 11.5 kyear) and the last climatic transition .…”
Section: Introductionmentioning
confidence: 99%